A NEW SPECIES OF ERIOCAULON (ERIOCAULACEAE) FROM THE SOUTHERN WESTERN GHATS OF KERALA, INDIA. (3rd July 2020) - Francis, D.; Mohan, V.; Venugopal, D. K.; Nampy, S.
Abstract : A new species of Eriocaulon, E. vamanae, is described from the southern Western Ghats of Kerala, India. It resembles Eriocaulon nepalense var. luzulifolium (Mart.) Praj. & J.Parn. but differs in the shape of its involucral bracts and receptacle, the fusion of the sepals in male flowers, the shape and indumentum of the sepals in female flowers, the size and indumentum of the petals in female flowers, and the seed coat appendages. Eriocaulon vamanae is so far known only from the type locality, Meesapulimala in Idukki District, Kerala, and is assessed as 'Critically Endangered' according to the IUCN's Red List Categories and Criteria .